Advanced Python development : using powerful language features in real-world applications - Wilkes, Matthew (Apress, 2020)
This book builds on basic Python tutorials to explain various Python language features that arent routinely covered: from reusable console scripts that play double duty as micro-services by leveraging entry points, to using asyncio efficiently to collate data from a large number of sources. Along the way, it covers type-hint based linting, low-overhead testing and other automated quality checking to demonstrate a robust real-world development process. Some powerful aspects of Python are often documented with contrived examples that explain the feature as a standalone example only. By following the design and build of a real-world application example from prototype to production quality you'll see not only how the various pieces of functionality work but how they integrate as part of the larger system design process. In addition, you'll benefit from the kind of useful asides and library recommendations that are a staple of conference Q & A sessions at Python conferences as well as discussions of modern Python best practice and techniques to better produce clear code that is easily maintainable. Advanced Python Development is intended for developers who can already write simple programs in Python and want to understand when its appropriate to use new and advanced language features and to do so in a confident manner. It is especially of use to developers looking to progress to a more senior level and to very experienced developers who have thus far used older versions of Python. You will: Understand asynchronous programming Examine developing plugin architectures Work with type annotations Review testing techniques Explore packaging and dependency management.